PENGARUH INDIAN OCEAN DIPOLE (IOD) TERHADAP SEBARAN POLA ANGIN DI BANDARA DEPATI AMIR PANGKALPINANG - Bais Ridwan, Muhamad (Pusdiklat BMKG, 2024)
The results of the NTSC investigation say that some of the factors that influence aviation accidents are human, technical, environmental, and facility factors. Surface wind conditions on the runway are one of the critical meteorological aspects for flight safety. This study aims to understand the surface wind distribution pattern during the Indian Ocean Dipole (IOD) phase and reduce the potential for aircraft accidents at Depati Amir Airport - Pangkalpinang. IOD itself is a weather phenomenon in the Indian Ocean that affects weather conditions in the surrounding area. The results of research conducted using the windrose method with surface wind data from 2011 to 2020 show that each phase of the IOD has a different impact on the distribution of wind patterns at Depati Amir Airport. Positive IOD tends to cause an increase in the percentage of wind speed up to 13.7% of the mean even though the dominant wind direction tends to be the same as the mean. Neutral IOD tends to cause a decrease in the percentage of wind speed from the mean even though the dominant wind direction tends to have a similar pattern to the mean. Meanwhile, Negative IOD causes a shift in the dominant wind direction at Depati Amir Airport by 45o - 90o counterclockwise from the mean. In addition, the Negative IOD also caused a decrease in the percentage of wind speed in all wind speed categories up to 32.7%.